Rise of graphene in novel piezoresistive sensing applications: A review on recent development and prospect - Khalid, Muhammad Yasir; Umer, Rehan; Zweiri, Yahya H.; Kim, Jang-Kyo (Materials science & engineering. R, Reports : a review journal, 2025)
Remarkable progress in developing graphene-based nanomaterials has provided vital breakthroughs in many fields including energy, environment, and sensor technologies. Thanks to its excellent piezoresistive characteristics to detect mechanical deformations with enhanced signal transfer capabilities, graphene has found extensive applications as strain and pressure sensors—important components for flexible devices, wearable electronic skin and human-machine interfaces. Given many existing review articles on similar subjects in the literature, this paper is dedicated to reviewing the current state-of-the-art developments and prospects of graphene-based, piezoresistive strain and pressure sensors, focusing mainly on their important performance criteria, fabrication strategies and novel applications. It covers the details of how their key performance can be improved through rational design and facile fabrication approaches specifically for flexible and wearable electronics. The discussion in this review serves as concrete proof of enhanced multifunctionality of graphene piezoresistive sensors in wearable technologies. Current challenges and opportunities for emerging applications of graphene sensors in smart devices are highlighted. [Display omitted]